Fostering creativity and performance through authentic leadership in educational institutions - Wen-Ling Hsu; Andri Dayarana K. Silalahi; Ixora Javanisa Eunike; Do Thi Thanh Phuong (Cogent Social Sciences, 2024)
Leadership is essential for organizational success, especially in educational institutions. This study aims to explore how authentic leadership can enhance employee performance and creativity. Previous research has often overlooked the significant role of authentic leadership in fostering higher levels of creativity and performance within educational organizations. Therefore, there is a clear need for more comprehensive research to gain deeper insights into how the principles of authentic leadership – such as self-awareness, relational transparency, internalized moral perspective and balanced processing – can elevate the performance and creativity of both staff and educators. This study collected data from teachers and staff at schools in Indonesia (N = 402) and tested the research model and hypotheses using Structural Equation Modeling via Smart-PLS 4.0. The findings indicate that attributes such as self-awareness, relational transparency, internalized moral perspective and balanced influence significantly impact job performance. These results higlight the importance of authentic leadership practices for school principals, teachers and staff in optimizing school effectiveness through appropriate organizational processes. Additionally, the findings emphasize the crucial role of fostering creativity and enhancing overall performance within the school environment. The study suggests that school principals should adopt and implement authentic leadership principles to improve the overall effectiveness of their educational institutions.